Nickel-Catalyzed Reductive Cross-Coupling of Benzyl Halides with Aryl Halides - Zhang, Qingchen; Wang, Xuan; Qian, Qun; Gong, Hegui (Synthesis, 2016)
Systematic studies of the coupling of benzylic with aryl halides are presented. The optimized reaction conditions for electron-deficient aryl halides cannot be applied to the electron-rich or neutral counterparts, and vice versa. The excellent functional group tolerance and broad substrate scope may enable the current work to be useful for the construction of diaryl methane products.
Keywords: nickel; cross-coupling; arylation; alkyl halide; catalysis